The Effect of E-Trust and Marketing Public Relation on Consumer E-Loyalty of Lazada - Hidayah, Riski Taufik (Jurnal Ilmu Ekonomi Terapan, 2017)
The purpose of this research is to find the impact of e-trust and marketing public relations toward e-loyalty of consumers at the online marketplace Lazada. This research is triggered by the decreasing percentage of Top Brand Award on every category Lazada is in. Even though Lazada as an online service provider has done several efforts to improve customer trust with quality improvement and developing small and micro-enterprises. The methods used in this research is descriptive and verificative. The population in this research are Lazada consumers who have the intention to repurchase from Lazada. The sampling technique in this research is purposive sampling, with the number of samples are 200 people. Path Analysis is used to analyze and to understand the correlation whether it is simultaneous or partial.